2019
DOI: 10.1038/s41467-019-08616-0
|View full text |Cite
|
Sign up to set email alerts
|

On the predictability of infectious disease outbreaks

Abstract: Infectious disease outbreaks recapitulate biology: they emerge from the multi-level interaction of hosts, pathogens, and environment. Therefore, outbreak forecasting requires an integrative approach to modeling. While specific components of outbreaks are predictable, it remains unclear whether fundamental limits to outbreak prediction exist. Here, adopting permutation entropy as a model independent measure of predictability, we study the predictability of a diverse collection of outbreaks and identify a fundam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
163
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(180 citation statements)
references
References 61 publications
(104 reference statements)
3
163
0
1
Order By: Relevance
“…). In epidemiology, a recent study on the information‐theoretic limits to forecasting of infectious diseases concluded that, for most diseases, the forecast horizon is often well beyond the time scale of outbreaks, implying that prediction is likely to succeed (Scarpino and Petri ).…”
Section: Discussionmentioning
confidence: 99%
“…). In epidemiology, a recent study on the information‐theoretic limits to forecasting of infectious diseases concluded that, for most diseases, the forecast horizon is often well beyond the time scale of outbreaks, implying that prediction is likely to succeed (Scarpino and Petri ).…”
Section: Discussionmentioning
confidence: 99%
“…The 24 transmissibility depends on the biological properties of the coronavirus, as 25 well as the contact patterns which can be intervened at the national or social 26 levels in populations. We hypothe- 28 sized that there could be a significant reduction of transmissibility with time 29 which is in accordance with the public health interventions in Wuhan and 30 other provinces. We hypothe- 28 sized that there could be a significant reduction of transmissibility with time 29 which is in accordance with the public health interventions in Wuhan and 30 other provinces.…”
mentioning
confidence: 52%
“…25 Zhang et al [31] proposed a measurement to state the efforts of users on Twitter to get 26 their information spreading. They found that small fraction of users with special 27 performance on participation can gain great influence, while most other users play a 28 role as middleware during the information propagation. 29 Up to now, most researches are focused on macro level of spreading prediction, but 30 few on micro level.…”
Section: Introductionmentioning
confidence: 99%
“…In [28], the researchers studied the predictability of a 15 Many state-of-the-art researches focus on predicting infection scale or threshold.…”
mentioning
confidence: 99%
See 1 more Smart Citation